Design and Experimental Research on Sealing Structure for a Retrievable Packer - Yang Liu; Zhanghua Lian; Junwen Chen; Shengping Kuang; Yisheng Mou; Yuhai Wang (Shock and Vibration)
In order to reduce the failure accidents of conventional packers, a kind of sealing structure of retrievable packers is designed, which can provide reference for optimizing the sealing performance and pressure capacity of packers. And theoretical calculation and experimental research on their sealing performance and pressure capacity are carried out through the finite element analysis on the contact with large deformation based on Abaqus and experimental study. The results show that the upper packer is subjected to greater stress and mainly plays a sealing role in the sealing process. In order to improve the sealing performance of the packer, the height of the upper and lower packer should be preferentially selected about 60 mm, the height of the middle rubber cylinders should be about 50 mm, and the thickness of the packer should be about 21 mm. The newly designed rubber cylinders can meet 150°C. The newly designed rubber cylinders can meet the sealing function and pressure bearing function under the condition of 10,000 Psi and 150°C. The newly designed rubber cylinder can satisfy the function of sealing and pressure-bearing under 140°C and 10,000 Psi. The whole experiment shows that the capacity of bearing pressure and sealing is stable, which can better meet the requirements of field use.